2017
DOI: 10.17129/botsci.887
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism analysis in some Algerian <em>Opuntia</em> species using morphological and phenological UPOV descriptors

Abstract: Background: In the present study, we have investigated the morphological variation in a set of five Opuntia species from the Algerian steppes using 49 UPOV descriptors. Questions: Which of the 49 descriptors that can be used as powerful estimators of the phenotypic diversity within Opuntia species? How is the morphological diversity patterned in Algerian Opuntia? Species study/ Mathematical model: Opuntia ficus-indica, Opuntia amycleae, Opuntia streptacantha, Opuntia engelmannii, Opuntia robusta. Principal Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In Algeria, PCA and Hierarchical Cluster Analysis were conducted on a set of five Opuntia species using 49 descriptors. The analysis revealed distinct differences between the species and identified eight key descriptors crucial for their classification; these findings have important implications for the selection and conservation of Opuntia species in Algeria (Hadjkouider et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…In Algeria, PCA and Hierarchical Cluster Analysis were conducted on a set of five Opuntia species using 49 descriptors. The analysis revealed distinct differences between the species and identified eight key descriptors crucial for their classification; these findings have important implications for the selection and conservation of Opuntia species in Algeria (Hadjkouider et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…The present study revealed the morphological and phenological diversity of the Opuntia genus in Tenerife (Canary Islands, Spain) using 52 descriptors of the UPOV and chemical composition. Hadjkouider et al [30] studied forty-nine morphological descriptors in five Opuntia species cultivated on Algerian steppes. Other authors, such as Gallegos-Vázquez et al [29,44], Erre and Chessa [45], Mejía et al [46], and Chalak et al [14], performed 24, 38, 23, and 23 descriptors, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hadjkouider et al [30] reported that only a few descriptors have an effective discriminating capacity. In their study, two quantitative descriptors (length of flower and length of the longest spine per cladode) and six qualitative descriptors (time of beginning of flowering, time of harvest maturity, main color of the spine, main color of the fruit surface, color of the fruit flesh, and firmness of the fruit flesh) were identified as differential parameters in Opuntia ficus-indica, Opuntia amyclaea, Opuntia streptacantha, Opuntia robusta, and Opuntia engelmannii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the consumption of fresh fruit causes the production of a huge amount of peel that consequently leads to serious environmental pollution problems and a generalized loss of nutritional value. Fruit peel is an abundant and renewable resource, suitable for animal feed as an important fodder crop during low feed availability periods following drought and dry seasons . Several projects and local programs have supported the diverse application of OFI (in food and pharmaceutical areas).…”
Section: Introductionmentioning
confidence: 99%